Analisis Kinerja Rele Proteksi Gic Md71bh Pada Trainer AMF-ATS Hybrid Berbasis PLC Omron CP1E - Joko Sambodo (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In industrial and household settings, three-phase electrical systems are widely used. However, their usage often encounters Voltage disturbances such as low Voltage, overVoltage, and Voltage imbalance between phases R-N, S-N, and T-N. Such disturbances can disrupt activities requiring Voltage stability and may damage electronic devices. Based on the above background, the author chose the research topic Phase Failure Relay, aimed at protecting electrical equipment in households and industries. This is achieved using the GIC MD71BH protection relay to detect overVoltage or Voltage drops and then sending a signal to the PLC to switch the load to an alternative power source (solar power plant/generator). The results of this study indicate that the function of the Phase Failure Relay in the AMF-ATS hybrid panel simulator installation based on Omron PLC is crucial for disconnecting power from the main source (PLN) during Voltage disturbances. It also provides an input signal to the PLC to process the transfer of the load to a backup power source. The protection values are set at under-Voltage -10% of the nominal Voltage and over-Voltage +10% of the nominal Voltage. From the testing of the phase failure relay with the designed wiring, the protection relay functions effectively, disconnecting power from the main PLN source during Voltage disturbances.